Mediating Role of Corporate Governance on the Effect of Earnings Management and Financial Risk on Firm Value - Defriko Gusma Putra; Yodi Pratama; Indra Mulia Pratama; Nisha Selvia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
This study is to determine the effect of earnings management with discretionary accruals indicators and financial risk with debt to equity ratio (DER) indicators on firm value with price earning ratio (PER) indicators with corporate governance as a mediating variable with managerial ownership and institutional ownership indicators. The research method is quantitative with the object of research being the Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2015-2017 with all out observations of 87 information. The test results show that earnings management variables have a negative and significant effect on firm value. The financial risk variable has a negative and significant effect on firm value. The corporate governance variable has a positive and significant effect on firm value. The effect of earnings management on firm value has a negative effect on corporate governance as a mediating variable. This shows that corporate governance can reduce earnings management actions. The effect of financial risk on firm value has a negative effect by the company's administration as a mediating variable. This shows that corporate governance can reduce financial risk. The results of this study provide a theoretical contribution that supports agency theory and corporate governance, which in turn makes a practical contribution to the implementation of good corporate governance in companies.